(untitled) (Scientific journal of the Fergana State University, 2024)
According to the state higher education standard, a specialist in the field of physical culture (i.e., a bachelor) must possess knowledge and skills from the cycle of general humanitarian and socio-economic sciences in professional education. Such a specialist should understand the role of physical culture in human development and in the preparation of professionals. They must also have a system of practical skills and abilities that ensure the preservation and strengthening of health, the development and improvement of psychophysical capabilities and qualities, and the ability to independently shape their own destiny in physical culture. Additionally, they must accumulate experience in using physical education and sports activities to achieve life and professional goals.